ESTIMATION OF TOTAL PHENOL IN SOME MEDICINAL PLANTS OF MARATHWADA REGION IN MAHARASHTRA - Kadam, V B; SONAWANE, V B; TAMBE, S S; KADAM, U B (Journal of Drug Delivery and Therapeutics, 2013)
AnÂ attemptÂ hasÂ beenÂ madeÂ hereÂ toÂ investigateÂ occurrenceÂ ofÂ totalÂ phenol inÂ the leaves , barkÂ andÂ woodÂ Â ofÂ Butea monosperma ÂLam, MadhucaÂ indica Gmel,Â Mimusops elengi Linn and Syzygium cumini Linn. are medicinally important plants of Marathwada region in Maharashtra. ComparativeÂ accountÂ ofÂ totalÂ phenolÂ contentÂ ofÂ leaves ,bark and wood ofÂ fourÂ speciesÂ revealedÂ that , MadhucaÂ indica wereÂ richÂ ( range 2.156Â to 4.410Â mg / g dry wt. )Â than Butea monosperma (range 1.987 to 4.138 mg / g dry wt.) Â, Mimusops elengi (range 2.601 to 3.438 mg / g dry wt.)Â and Syzygium cumini (range 1.621 to 3.330Â mg / g dry wt. )Â in all seasons. Key words:Â Total Phenol, Medicinal Plants, Marathwada region.